THE IMPACT OF “TRUMP’S POLICIES” ON ECONOMIC GROWTH IN SOUTHEAST ASIA: SYSTEMATIC LITERATURE REVIEW APPROACH - Muspida; Hermi Oppier; Dientje Rumerung; Hendri Dony Hahury (RADJA PUBLIKA, 2026)
This study aims to analyze the complex impact of President Donald Trump's